Amitriptyline Decreases GABAergic Transmission in Basal Forebrain Neurons Using an Optogenetic Model of Aging - Bang, Eunyoung; Tobery, Angelika; Montgomery, Karienn S.; Fincher, Annette S.; Earnest, David J.; Murchison, David A.; Griffith, William H. (Frontiers in Aging Neuroscience, 2021)
The antidepressant drug amitriptyline is used in the treatment of clinical depression and a variety of neurological conditions such as anxiety, neuropathic pain disorders and migraine. Antidepressants are associated with both therapeutic and untoward effects, and their use in the elderly has tripled since the mid-1990s. Because of this widespread use, we are interested in testing the acute effects of amitriptyline on synaptic transmission at therapeutic concentrations well below those that block voltage-gated calcium channels. We found that 3 M amitriptyline reduced the frequency of spontaneous GABAergic inhibitory postsynaptic currents (IPSCs) and reduced quantal content in mice at ages of 7-10 mo. and 23-25 mo., suggesting a presynaptic mechanism of action that does not diminish with age. We employed a reduced synaptic preparation of the basal forebrain (BF) and a new optogenetic aging model utilizing a bacterial artificial chromosome (BAC) transgenic mouse line with stable expression of the channelrhodopsin-2 (ChR2) variant H134R specific for GABAergic neurons [VGAT-ChR2(H134R)-eYFP]. This model enables optogenetic light stimulation of specific GABAergic synaptic terminals across aging. Age-related impairment of circadian behavior was used to confirm predictable age-related changes associated with this model. Our results suggest that low concentrations of amitriptyline act presynaptically to reduce neurotransmitter release and that this action is maintained during aging.